Curso de medicina: fonte de satisfação ou ansiedade? Um estudo sobre a saúde mental de alunos do primeiro ano de medicina - Figueiredo, Danielle Soraya da Silva (2021)
Medical students experience high levels of anxiety and other mental disorders which have been associated with overwork, sleep deprivation, peer pressure, and other aspects of medical education. The aim of the study was to analyze the frequency of mental health disorders (anxiety, worry and depression) among first year medical students. Material and Methods: This is a cross-sectional study, carried out during the first-year of medical school at Midwestern Parana State University (UNICENTRO), in the city of Guarapuava-PR, Brazil. Clinical and sociodemographic information were collected. All students underwent psychological assessment at the beginning and end of the first year of the medical course. Psychological reports included BDI II - Beck Depression Inventory; EPD - Depressive Thoughts Scale; Generalized Anxiety Disorder Questionnaire (TAG) and Penn State University Worry Questionnaires. Saliva was collected to measure cortisol. Results and Conclusion: Our data confirm the high levels of emotional disorders, such as anxiety, worry and depression among students in the first year of medical school. We observed that the students got into university having severe anxiety, mild depression, low self-esteem and deficit in the functional relationships, which got worse during the first year medical course (p=0.001). These data demonstrate the need to adapt the medical school to receive the freshmen, beside the importance of rethinking the psycho-emotional support during the medical course.